The Influence of Brand Image, Perceived Service Quality, Perceived Value, and Customer Satisfaction on Customer Loyalty at Clinic a Tangerang - Khairunisa, Caesilia; Meilani, Yohana F. Cahya Palupi (Eduvest - Journal of Universal Studies, 2025)
As the number of primary care clinics increases, competition to be patients' first choice intensifies, with service quality playing a crucial role in influencing patient satisfaction and loyalty. In such a competitive environment, customer loyalty is vital, closely tied to customer satisfaction. This study analyzes the influence of brand image, perceived value, perceived service quality, customer satisfaction, and customer loyalty at Clinic A Tangerang. Data were collected from 147 respondents using a non-probability sampling technique and analyzed using SmartPLS 4.1.0.8 software with PLS-SEM. The results indicate that brand image does not affect customer satisfaction (p = 0.823 > 0.05), while perceived service quality (p = 0.000 < 0.05) and perceived value (p = 0.000 < 0.05) significantly influence satisfaction. Brand image (p = 0.000 < 0.05) and perceived value (p = 0.004 < 0.05) positively impact loyalty, but perceived service quality does not (p = 0.496 > 0.05). Customer satisfaction significantly influences loyalty (p = 0.018 < 0.05). These findings underscore the importance of enhancing service quality and perceived value to boost patient satisfaction and loyalty, providing actionable insights for Clinic A Tangerang to strengthen its competitive position.